Transcriptomic Analysis Reveals the Involvement of lncRNA–miRNA–mRNA Networks in Hair Follicle Induction in Aohan Fine Wool Sheep Skin - Zhao, Ranran; Li, Jing; Liu, Nan; Li, Hegang; Liu, Lirong; Yang, Feng; Li, Lanlan; Wang, Yuan; He, Jianning (Frontiers in Genetics, 2020)
ABSTRACT Long non-coding RNAs (lncRNA) and microRNAs (miRNA) are new found classes of non-coding RNAs(ncRNAs) that are not translated into proteins but regulate various cellular and biological processes. In this study, we conducted a transcriptomic analysis of ncRNA and mRNA expression in Aohan fine wool sheep (AFWS) at different growth stages (embryonic day 90, embryonic day 120, and the day of birth), and explored their relationship with wool follicle growth. In total, 461 lncRNAs, 106 miRNAs, and 1,009 mRNAs were found to be differentially expressed during the three stages of wool follicle development. Gene Ontology (GO) enrichment and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis were performed to clarify the roles of the differentially expressed lncRNA, miRNA, and mRNA in the different stages of wool follicle development. Quantitative real-time PCR (qRT-PCR) was used to validate the results of RNA-seq analysis. LncRNA (MSTRG.223165) was found to act as a competing endogenous RNA (ceRNA) and may participate in wool follicle development by acting as an miR-21 sponge. Network prediction implicated the MSTRG.223165-miR-21-SOX6 axis in the wool follicle development. The targeting relationships of miR-21 with SOX6 and MSTRG.223165 were validated in dual-luciferase assays. This is the first report indicating the association of the lncRNA-miRNA-mRNA network with wool follicle development in AFWS. This study provides new insights into the regulation of the wool follicle growth and represents a solid foundation for wool sheep breeding programs.